The Cooperative Re-Engagement Controlled trial (CoRECT): A randomised trial to assess a collaborative data to care model to improve HIV care continuum outcomes - Robyn Neblett Fanfair (Elsevier, 2021)
Background: Persons with HIV (PWH), aware of their HIV infection but not in care account for an estimated 42.6% of HIV transmissions in the United States. Health departments and clinics implemented a collaborative data-to-care strategy to identify persons newly out-of-care with the objective of increasing re-engagement, retention in medical care, and viral load suppression Methods: A multi-site, prospective randomised trial was conducted to identify newly out-of-care PWH using surveillance and clinic data in Connecticut (CT), Massachusetts (MA) and Philadelphia (PHL). All out-of-care participants were randomised to receive standard of care or an active public health intervention. Re-engagement in care was defined as having a documented CD4 count and/or HIV viral load within 90 days of randomization. Retention was defined as having at least two CD4 count and/or HIV viral load results ≥ 3 months apart within 12 months of randomization, and viral load suppression as having a viral load < 200 copies/ml within 12 months of randomization. Findings: Between August 2016 and July 2018, 1893 out-of-care participants were randomised from CT (N = 654), MA (N = 630), and PHL (N = 609). Participants were male (69.5%), non-Hispanic Black (48.3%) and men who have sex with men (38.8%). Re-engagement within 90 days was significantly higher for the intervention group overall and in all three jurisdictions (All sites: 54.9% vs 42.1%, p < 0.0001; CT: 51.2% vs 41.9%, p = 0.02; MA: 52.7% vs 44.1%, p = 0.03; PHL 61.2% vs 40.3%, p < 0.0001). Retention in care over 12 months improved overall (p = 0.04). Median time to viral suppression was reduced overall (p = 0.0006); CT (p = 0.32), MA (p = 0.02) and PHL (p < 0.0001). Interpretation: This trial showed that a collaborative, data-to-care strategy, and active public health intervention led by health departments significantly increases the proportion of PWH re-engaged in HIV care and may improve retention in care and decrease time to viral suppression.